Implementing a General Practice-Based Link Worker Intervention for People with Multimorbidity During the Covid-19 Pandemic- a Mixed Methods Process Evaluation of the LinkMM RCT - Bridget Kiely; Ivana Keenan; Sonali Loomba; Natalie Mack; Vivienne Byers; Emer Galvin; Muireann O’Shea; Patrick O’Donnell; Fiona Boland; Barbara Clyne; Eamon O’Shea; Susan M. Smith; et al. (International Journal of Integrated Care)
Background: Social prescribing link workers support patients to connect with community resources to improve their health and well-being. These roles are prominent in policy, but there is limited evidence on what support is provided by link workers and what factors influence implementation of link worker interventions. Methods: A convergent, mixed methods process evaluation of an exploratory randomised trial of a one-month general practice-based link worker intervention targeting adults with multimorbidity in deprived areas. Qualitative data from interviews with 25 patients, 10 general practitioners, 10 link workers and eight community resource providers were thematically analysed and integrated with quantitative data to explore implementation, adaptations, context and mediators. Results: GPs reported recruitment challenges related to complicated research documentation and COVID-19 related workload and restrictions. Despite most components of the intervention being delivered, the intervention was considered too short to support people with complex needs to connect with resources, particularly in the context of COVID-19 restrictions. Timing of the referral, location within general practice and link workers’ person-centred approach facilitated the intervention. Conclusions: For future evaluations, recruitment procedures need to be simplified and integrated into everyday practice. For patients with multimorbidity, a longer intervention is indicated to achieve connection with community resources.